From the sea to the table: The environmental impact assessment of fishing, processing, and end‐of‐life of albacore in Cantabria. (20th December 2022) - Fernández‐Ríos, Ana; Ceballos‐Santos, Sandra; Laso, Jara; Campos, Cristina; Cristóbal, Jorge; Margallo, María; Aldaco, Rubén; Ruiz‐Salmón, Israel
Abstract: Cantabria, a small coastal region of Northern Spain, is one of the biggest producers of gourmet tuna cans in Europe. The fish capture in the Cantabrian Sea and the subsequent transformation in a local processing plant give distinction to this product, which is widely marketed in cans of 105 g of net weight. This work evaluates for the first time the environmental profile of the whole supply chain of this product, from fishing, processing, and waste valorization to inter‐stage transport and packaging management in the end‐of‐life. To this end, the life cycle assessment methodology was applied considering primary data from the stakeholders involved in the supply chain and analyzing the seven most studied categories in this sector. Results revealed that fishing and processing accounted for the majority of the environmental impacts, while valorization and end‐of‐life treatments only avoid less than 10% of the burdens. The most important findings are focused on the high dependence on fuel use, identified as a hotspot in most stages although low compared to other fisheries, and on the intensive use of resources, especially sunflower oil, which contributes more than 70% of the impact on the global warming potential of the processing. This current framework forces the enhancement of the efficiency of a sector that attempts to engage the challenge of societal sustainability, by identifying the critical points and guiding policy makers on the path to sustainable development.